Effect of land cover and landscape fragmentation on anopheline mosquito abundance and diversity in an important Colombian malaria endemic region (2020)
ABSTRACT : Landscape structure influences the distribution and abundance of anopheline mosquitoes and has an indirect impact on malaria transmission. This work aimed to determine the effect of land cover and landscape fragmentation on anopheline mosquito abundance and diversity in an important Colombian malaria endemic area, the Bajo Cauca region. Diversity indices were calculated for Anopheles mosquitoes collected in various localities of the region. Land cover types were characterized using orthorectified aerial photographs to estimate landscape metrics. The relationship between landscape fragmentation and species diversity was evaluated by regression analysis. The correlation between species abundance and land cover types was determined using canonical correspondence analyses. Results showed a statistically significant tendency for a lower diversity of the Anopheles community in landscapes with higher patch number, patch density and effective mesh size. For most species, there was evidence of a significant relationship between species abundance and land covers modified by anthropic activities which generate forest loss. These results indicate that activities that modify the landscape structure and land cover composition generate changes that affect the spatial distribution and composition of epidemiologically-important Anopheles species, which may impact malaria distribution in a region. This information is useful to guide control interventions that promote unfavorable landscapes for malaria vector propagation.